2017
DOI: 10.1136/bmjpo-2017-000118
|View full text |Cite
|
Sign up to set email alerts
|

Bowel preparation for elective procedures in children: a systematic review and meta-analysis

Abstract: ObjectiveReviews have investigated preparation for colonoscopy, but not for surgery, They are also often limited to patients up to 16 years, despite many paediatric gastroenterologists caring for older patients. We carried out a systematic review investigating the optimum bowel preparation agents for all indications in children and young people.DesignA Cochrane format systematic review of randomised controlled trials (RCTs). Data extraction and assessment of methodological quality were performed independently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 21 publications
4
22
0
2
Order By: Relevance
“…As a result, the rate of children from the PEG-ELS group being unable to successfully complete the bowel preparation was higher than that in the sodium picosulphate/magnesium citrate group and the willingness to repeat the preparation if needed was lower when compared with the two other groups. Our results, in terms of efficacy, tolerability, and safety, are comparable with the data presented in a recently published meta-analysis on bowel preparation in children that included two studies comparing PEG and sodium picosulphate/magnesium citrate [2].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As a result, the rate of children from the PEG-ELS group being unable to successfully complete the bowel preparation was higher than that in the sodium picosulphate/magnesium citrate group and the willingness to repeat the preparation if needed was lower when compared with the two other groups. Our results, in terms of efficacy, tolerability, and safety, are comparable with the data presented in a recently published meta-analysis on bowel preparation in children that included two studies comparing PEG and sodium picosulphate/magnesium citrate [2].…”
Section: Discussionsupporting
confidence: 87%
“…Overall, the best bowel regimen in children before the elective colonoscopy with regard to the preparation's palatability, volume of the solution, ease at taking, and willingness to repeat was the NaPico+MgCit group. The results are in line with previous studies confirming that bowel cleansing with picosulphate/magnesium citrate was better tolerated and accepted than protocols with polyethylene glycol among children between 10 and 18 years of age [2,9,[12][13][14].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The studies that compare the efficacy of PEG and NP in children are limited. A metaanalysis including two studies that compare PEG and NP in 63 participants found no difference in adequacy of bowel preparation (6)(7)(8). Similarly, colonoscopy time and amount of suctioned fluid were not different between two groups in our study.…”
Section: Discussionsupporting
confidence: 42%
“…The tolerability of PEG was usually reported as poor, because it requires consumption of large amount of fluid and necessitates the use of nasogastric (NG) tube (6). One disadvantage of our study is that we did not evaluate the use of NG tube in our patients.…”
Section: Discussionmentioning
confidence: 96%